2021
DOI: 10.1177/24730114211012701
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of the Distal Tibiofibular Syndesmosis: A Systematic Review of Cadaveric Studies

Abstract: Background: This investigation’s purpose was to perform a systematic review of the literature examining the biomechanics of the ligaments comprising the distal tibiofibular syndesmosis with specific attention to their resistance to translational and rotational forces. Although current syndesmosis repair techniques can achieve an anatomic reduction, they may not reapproximate native ankle biomechanics, resulting in loss of reduction, joint overconstraint, or lack of external rotation resistance. Armed with a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…We had considered the possibility that fixing the Tillaux fracture may provide sufficient stability to the syndesmosis such that syndesmotic stabilization would not be necessary because AITFL has been shown to have a dominant role in stabilizing the distal TF syndesmosis 17 . However, after we fixed the Tillaux fracture, the distal TF syndesmosis was grossly unstable in the setting of soft-tissue stripping, attenuated AITFL, and injury to the other TF ligaments.…”
Section: Discussionmentioning
confidence: 99%
“…We had considered the possibility that fixing the Tillaux fracture may provide sufficient stability to the syndesmosis such that syndesmotic stabilization would not be necessary because AITFL has been shown to have a dominant role in stabilizing the distal TF syndesmosis 17 . However, after we fixed the Tillaux fracture, the distal TF syndesmosis was grossly unstable in the setting of soft-tissue stripping, attenuated AITFL, and injury to the other TF ligaments.…”
Section: Discussionmentioning
confidence: 99%
“…16 In a systematic review of cadaveric studies, it is found that IOL is the strongest syndesmotic ligament, and the AITFL has a dominant role in stabilizing the DTFS to external rotation force and therefore external rotation stress test is the most sensitive test to recognize an AITFL tear. 17 In a biomechanical study, it was found that the AITFL provided 35%, the transverse tibiofibular ligament or deep portion of the PITFL 33%, the IOL 22%, and the PITFL 9% of the overall stability. 18 In a cadaveric study evaluating ligamentous structures of the syndesmosis it was found that a diastasis of 2.3 mm occurred with sectioning of the AITFL alone, 5.5 mm with additional sectioning of the IOL, and 7.3 mm after additional sectioning of the PITFL.…”
Section: Anatomymentioning
confidence: 99%
“…A relevant threshold value of relative motion between the two bones of > 2mm was determined. This value is based on a native physiological diastasis of about 1 mm in mediolateral direction, which is known from the literature [43][44][45].…”
Section: Biomechanical Evaluation Of the Syndesmotic Diastasismentioning
confidence: 99%